Central Simulation Model W8D-2010 of the Polish Economy - Florczak, Waldemar; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article presents the structure and main economic mechanisms mapped by the W8D-2010 model of the Polish economy. The model itself is a continuation of W8D series of models that have been constructed at the Chair of Econometric Models and Forecasts at the University of Lodz, under the scientific supervision of prof. dr hab. Władysława Welfe. Model W8D-2010 is marked by many new solutions – both theoretical and empirical – that are absent in previous versions, which is explicitly proved by the model's size: considerably bigger than that of its predecessors. Besides, the model's structure enables its extension in order to e.g. incorporate selected aspects of sustainable development, which is going to constitute further research objectives.